Rheological Abnormalities in Human Erythrocytes Subjected to Oxidative Inflammation - Maruyama, Toru; Hieda, Michinari; Mawatari, Shiro; Fujino, Takehiko (Frontiers in Physiology, 2022)
Erythrocytes are oxygen carriers and exposed to redox cycle in oxygenation and deoxygenation of hemoglobin. This indicates that circulating erythrocytes are vulnerable to the oxidative injury occurring under the imbalance of redox homeostasis. In this review article, two topics are presented concerning the human erythrocytes exposed to the oxidative inflammation including septic and sterile conditions. First, we demonstrate rheological derangement of erythrocytes subjected to acute oxidative injury caused by exogenous generators of reactive oxygen species (ROS). Erythrocyte filterability as whole-cell deformability has been estimated by the gravity-based nickel mesh filtration technique in our laboratory and was dramatically impaired in a time-dependent manner after starting exposure to the ROS generators, that is associated with concurrent progression of membrane protein degradation, phospholipid peroxidation, erythrocyte swelling, methemoglobin formation, and oxidative hemolysis. Second, we introduce an impairment of erythrocyte filterability confirmed quantitatively in diabetes mellitus and hypertension of animal models and patients under treatment. Among the cell geometry, internal viscosity, and membrane property as the three major determinants of erythrocyte deformability, erythrocyte membrane alteration is supposed to be the primary cause of this impairment in these lifestyle-related diseases associated with persistent oxidative inflammation. Excessive ROS trigger the inflammatory responses and reduce the erythrocyte membrane fluidity. Oxidative inflammation increasing erythrocyte membrane rigidity underlies the impaired systemic microcirculation, which is observed in diabetic and/or hypertensive patients. On the other hand, elevated internal viscosity caused by sickle hemoglobin polymerization is a primary cause of impaired erythrocyte filterability in sickle cell disease (SCD). However, oxidative inflammation is also involved in the pathophysiology of SCD. The physiologic level of ROS acts as signaling molecules for adaptation to oxidative environment, but the pathological level of ROS induces suicidal erythrocyte death (eryptosis). These findings provide further insight into the ROS-related pathophysiology of many clinical conditions.